2022
DOI: 10.1097/ta.0000000000003758
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of endothelial cell dysfunction persist beyond resuscitation in patients with hemorrhagic shock

Abstract: BACKGROUND:It has been shown that binds to and degrades syndecan-1 after hemorrhagic shock (HS) and contributes to endothelial dysfunction in vitro and in vivo. The objective of the current study was to assess longitudinal changes in miR-19b and syndecan-1 in HS patients. METHODS:Blood samples from HS patients (blood pressure <90 mm Hg and ≥2 U blood) were collected upon admission, completion of hemostasis, and after 24 hours for miR-19b (quantitative reverse transcription PCR) and syndecan-1 (enzyme-linked i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…It is possible that cryoprecipitate infusion itself could have contributed to the lack of mortality benefit. However, a recent study by Zeineddin et al examined organ dysfunction at 72 hours postinjury after using cryoprecipitate products in a mouse model of hemorrhagic shock and showed no adverse effects 26 . The extent of hemoperitoneum following liver injury and total blood removed to reach shock state also did not differ between groups (Table 1).…”
Section: Resultsmentioning
confidence: 93%
“…It is possible that cryoprecipitate infusion itself could have contributed to the lack of mortality benefit. However, a recent study by Zeineddin et al examined organ dysfunction at 72 hours postinjury after using cryoprecipitate products in a mouse model of hemorrhagic shock and showed no adverse effects 26 . The extent of hemoperitoneum following liver injury and total blood removed to reach shock state also did not differ between groups (Table 1).…”
Section: Resultsmentioning
confidence: 93%
“…There have been recent clinical studies demonstrating persistent changes in both syndecan-1 and VWF in hemorrhagic shock patients out to 24 hours, but we are not aware of any preclinical or clinical studies that have examined these parameters thru 72 hours postinjury. 23,24 We were interested in determining if the cryoprecipitate products would provide protection beyond the early postresuscitation phase. There are limited mouse models of hemorrhagic shock that extend beyond the immediate postresuscitation phase.…”
Section: Discussionmentioning
confidence: 99%
“…While there were significant reductions in gut histopathologic injury and preserved gut syndecan-1 immunostaining as well as reduced lung permeability, there were no persistent differences in indices of lung injury or syndecan-1 immunostaining, nor in liver function, kidney function, or systemic parameters of endothelial injury including syndecan-1 and VWF. There have been recent clinical studies demonstrating persistent changes in both syndecan-1 and VWF in hemorrhagic shock patients out to 24 hours, but we are not aware of any preclinical or clinical studies that have examined these parameters thru 72 hours postinjury 23,24 …”
Section: Discussionmentioning
confidence: 99%
“…Additional recent data show that EoT is a pathophysiologic state that persists over the first 24 hours after injury and remains a significant predictor of poor outcomes throughout this time period. 14 Using innovative proteomics approaches, Krocker et al 15 have shown that EoT is associated with a unique plasma proteome signature enriched in damage-associated molecular patterns (DAMPS), inflammatory mediators, and organ-specific intracellular markers, corroborating clinical evidence linking EoT with organ damage.…”
Section: Postinjury Morbidity and Mortality Linked To Eotmentioning
confidence: 93%